Volatilitas Indeks IDXMESBUMN Sebelum Dan Setelah Invansi Militer Rusia ke Ukraina - Ade Irma Suryani; Iqra Wiarta (Universitas Batanghari, 2022)
Volatility is a response from a portfolio or securities to a phenomenon that occurs. The response can be seen from the price changes of a number of stocks. The purpose of this study is to determine and analyze the return volatility of the Jakarta Islamic Index (JII) to the phenomenon of the Russian military invasion of Ukraine. The research method used is the analysis of different returns before and after the military invasion in the form of data 5 days before and 5 days after the invasion by using data sourced from the Indonesian stock exchange in the form of data as many as 17 companies that are members of the MESBUMN index. The results showed a significant value of 0.478, so there was a significant difference in the IDXMESBUMN index returns before and after the Russian military invasion.